KAJIAN FORMULASI BISKUIT JAGUNG DALAM RANGKA SUBSTITUSI TEPUNG TERIGU [Study on Corn Biscuit Formulation to Subtitute of wheat Flour] - Cynthia Gracia C.L; Sugiyono .; Bambang Haryanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2009)
The research was conducted to study the formulation of substitute by corn flour. The flour used roasted corn flour and unroasted corn flour. Results showed that biscuit’s made of 80 gr corn flour and 20 gr wheat flour were accepted by panelist’s and the best formulation was 80 gr corn flour, 20 gr wheat flour, 50 gr margarine, 50 gr sugar and 10 gr yellow egg both of two corn flour. Roasting treatment of corn flour significantly affected fat content, carbohydrate content and digestibility of protein of the biskuit.